"Life just keeps throwing lemons": the lived experience of food insecurity among Aboriginal people with disabilities in the West Kimberley. Issue 9 (1st September 2016) - Spurway, Kim; Soldatic, Karen
Abstract : This paper reports findings of a qualitative study conducted in collaboration with Aboriginal people with disabilities and their carers residing in the rural and remote Kimberley region of Western Australia, specifically the impact of chronic food insecurity on their daily lives. Nutritious food is important to maintaining health, particularly for Aboriginal people with disabilities who are at the greatest risk of a range of chronic health conditions, illnesses and secondary disability. In the remote areas of the West Kimberley, the high cost of living, including food expenses and the generally low incomes of residents mean that food insecurity is common. A large portion of the population living in remote and rural areas of the Kimberley is Aboriginal, and chronic illness and disability are twice as likely among this group. Lack of access to nutritious food has a cyclical interaction with disability, resulting in secondary impairments and ill health, which leads to greater economic exclusion and further food insecurity. Participants in this research consistently reported that they coped with food insecurity by fishing and crabbing on their traditional lands, "in country". This link between land sovereignty, food sovereignty and food security for Aboriginal Australians has echoes with global food sovereignty movements.